Xeractinol - A new flavanonol C-glucoside from Paepalanthus argenteus var. argenteus (Bongard) Hensold (Eriocaulaceae) - Dokkedal, Anne Ligia; Lavarda, Francisco; dos Santos, Lourdes Campaner; Vilegas, Wagner [UNESP] (Soc Brasileira Quimica, 2007)
New compound isolated from methanolic extract from the leaves of Paepalanthus argenteus var. argenteus (Bongard) Hensold was characterized as xeractinol, a new dihydroflavonol C-glucoside. The structure was elucidated on the basis of extensive spectroscopic analysis (1D and 2D NMR, MS, HREIMS, IR and UV). Ab initio electronic structure calculations support our proposal to the molecular structure. The dihydroflavonol herein isolated may serve as taxonomic marker of Paepalanthus subgenus Xeractis, because this flavonoid have not been reported in any other taxon of Eriocaulaceae.
Keywords: Paepalanthus argenteus var. argenteus; Eriocaulaceae; dihydroflavonol; xeractinol; ab initio calculations